THE PUBLIC RELATION LITIGATION STRATEGIES OF PT POS INDONESIA COMMUNICATION DIVISION IN DEALING WITH THE PROCUREMENT OF PERSONAL DATA TERMINAL - Widhiarti, dkk, Chandra Kesuma (EDUTECH, 2015)
Abstract, Strategic Public Relations is the way that has been planned to obtain a certain result. The result can be the purpose or goal of the objectives to be achieved by the company. Likewise with PT Pos Indonesia (Persero) which is handling the crisis through Litigation Public Relations. Crisis management must be done quickly and accurately so it requires careful planning. The purpose of this descriptive study was to determine strategies Public Relations Corporate Communications team, especially when the crisis is still being processed in court. Public Relations strategy is tailored to the stage of settling disputes in court. Keyword: Crisis, Litigation PR, Public Relations Public Relations Strategy Abstrak, Strategi Public Relations merupakan cara yang telah direncanakan untuk mendapatkan hasil tertentu. Hasil tersebut dapat berupa tujuan ataupun sasaran dari tujuan yang ingin dicapai oleh perusahaan. Demikian halnya dengan PT Pos Indonesia (Persero) yang tengah menangani krisis melalui Litigasi Public Relations. Penanganan krisis harus dilakukan dengan cepat dan tepat sehingga diperlukan perencanaan yang matang. Tujuan dari penelitian deskriptif ini adalah untuk mengetahui strategi Public Relations Tim Komunikasi Korporat khususnya ketika krisis masih diproses di Pengadilan. Strategi Public Relations tersebut disesuaikan dengan tahap penyelesaian perkara yang ada di Pengadilan.Kata Kunci: Strategi Public Relations, Litigasi PR, Krisis, Public Relations